185 Revisiting Comprehensive Geriatric Assessment in the Emergency Department. (16th September 2019) - Edge, Lucinda; O'Rourke, Brian; Cunningham, Conal; Horgan, Frances
Abstract: Background: In a large teaching hospital, a specialist interdisciplinary team identify frailty and begin comprehensive geriatric assessment of older adults in the Emergency Department (ED). This study aimed to determine the clinical utility of a range of measures: grip strength, calf circumference, frailty and functional mobility to evaluate whether they help to estimate the care pathways for patients. Objectives included: (1) To ascertain the prevalence of frailty and (2) To profile this population's demographics, falls history, calf circumference and grip strength. Methods: This was a cross-sectional study. Inclusion criteria were persons ≥ 70 who presented to ED weekdays during research hours 9:00 – 16:00, with Manchester triage score ≥ 3. Information on gait aids, social supports and falls in the past 6 months was self-reported. Grip strength was assessed using hydraulic hand-held dynamometry. Sarcopenia was measured using calf circumference as a proxy. Frailty was determined using the Clinical Frailty Scale (CFS). Functional mobility was assessed by an interdisciplinary team member. Onward referrals and admission to hospital were recorded. Data was analysed using SPSS statistics software. Results: One hundred and one participants were included, 39 male (38.6%) and 62 female (61.4%), mean age 79.3 years. Thirty-five percent (n=36) were considered Frail (a CFS score of ≥5), 35.6% (n=36) lived alone, 52.5% (n=53) used a gait aid. Outcomes included admission to hospital (27.7%, n=28) and discharge with onward referral (25.7%, n=26). The most common referral was community physiotherapy (11.9%, n=12). The population identified as frail were more likely to be female (p = 0.036), to use a gait aid (p = 0.001) and to have fallen within the past 6 months (p = 0.007). Conclusion: The prevalence of frailty was determined in this population and was not significantly associated with hospital admission, grip strength or calf circumference. A focus on alternative pathways to hospital admission with appropriate access to community services is recommended for individuals with frailty.